The Multiplicity of Citizenship Models and the Future Vision of the Citizen - Durzewska, Małgorzata (Journal of Applied Cultural Studies, 2016)
The study aims at the concept of culture in the context of cultural patterns which, in the process of the formation of culture, determine the ways of thinking, behavior and activities of each member of a culture. In the author’s opinion, these patterns may lead to the formation of various cultural patterns which frequently contradict one another, and finally to the strangeness which results from the different ideological assumptions within each culture. Such a concept of cultural patterns provides a new approach for studying culture, the creations and manifestations of culture and, last but not least, the functioning of the members of a culture. Contemporary concepts of the citizen usually focus on the liberal model of a civil society and to a lesser degree on communitarianism, while the other concepts are lean towards the cosmopolitan vision of the citizen of the world.